Optimized Hydraulic Fracturing Treatment In Oil Well With Very Low To High Permeability Reservoir - Susanto, Celine
This study evaluates fracture performance by presenting hydraulic fracturing treatment effect on very low, low, moderate, and high permeability of oil reservoir as a way to increase productivity. Hydraulic fracture stimulation optimal design is proposed for each reservoir properties based on the value of field fold of increase. Optimized well spacing is determined from the sensitivity of drainage area, so is the optimum number of wells to be treated by hydraulic fracturing. The analysis is also complemented with mass proppant sensitivity to design the optimum half-propped length. Study signifies that reservoir with very low permeability has highest incremental dimensionless productivity index and for optimum mass proppant injected to the well, every case has different amount of mass proppant needed because it depends on the value of dimensionless productivity index desired. This study will matter for the economic calculation of whether hydraulic fracturing is effective and profitable. Case of application for fracturing in X Field will be discussed.